Kejahatan Genosida Dalam Perspektik Hukum Pidana Internasional - Fikri Dwi Fadillah; Muhammad Zirly Annadziif (International Forum of Researchers and Lecturers, 2024)
International criminal law deals with extraordinary crimes, including the crime of genocide, which has been prohibited and regulated by various international treaties such as the 1948 Genocide Convention, the statute of the International Criminal Tribunals for the Former Yugoslavia (ICTY), the statute of the International Criminal Tribunals for Rwanda (ICTR), and the 1998 Rome Statute. This research aims to understand the crime of genocide in the context of International Law and its related dispute resolution methods. This research uses a doctrinal or normative juridical research approach. The results show that genocide crimes often arise as a result of the struggle for tribal rights which is a minority group. In addition, the existence of religious and racial fanaticism can also play a role in encouraging cultural discrimination that leads to the crime of genocide. In response to these crimes, International Law has developed regulations and dispute resolution mechanisms. This research provides an in-depth understanding of the root causes of the crime of genocide and highlights the role of International Law in addressing such acts. Dispute resolution methods, whether through peaceful or coercive means, become relevant in responding to the crime of genocide and upholding international justice. As such, this research contributes to further understanding of the complexity and urgency of addressing the crime of genocide within the framework of International Law.